Treatment of a mud pit by bioremediation. Issue 8 (August 2016) - Avdalović, Jelena; Đurić, Aleksandra; Miletić, Srdjan; Ilić, Mila; Milić, Jelena; Vrvić, Miroslav M
The mud generated from oil and natural gas drilling, presents a considerable ecological problem. There are still insufficient remedies for the removal and minimization of these very stable emulsions. Existing technologies that are in use, more or less successfully, treat about 20% of generated waste drilling mud, while the rest is temporarily deposited in so-called mud pits. This study investigated in situ bioremediation of a mud pit. The bioremediation technology used in this case was based on the use of naturally occurring microorganisms, isolated from the contaminated site, which were capable of using the contaminating substances as nutrients. The bioremediation was stimulated through repeated inoculation with a zymogenous microbial consortium, along with mixing, watering and biostimulation. Application of these bioremediation techniques reduced the concentration of total petroleum hydrocarbons from 32.2 to 1.5 g kg −1 (95% degradation) during six months of treatment.